2013
DOI: 10.1016/j.bmcl.2012.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-aminomethyl-4-phenyl-1-azabicyclo[2.2.1]heptanes via LiAlH4-induced reductive cyclization of 2-(4-chloro-2-cyano-2-phenylbutyl)aziridines and evaluation of their antimalarial activity

Abstract: 2-(4-Chloro-2-cyano-2-phenylbutyl)aziridines were employed for the one-step stereoselective construction of both endo- and exo-2-aminomethyl-4-phenyl-1-azabicyclo[2.2.1]heptanes as new azaheterobicyclic scaffolds via a double LiAlH(4)-induced reductive cyclization protocol. Antiplasmodial assessment of these 1-azabicyclo[2.2.1]heptanes revealed moderate to good activities in the micromolar range, with the exo-isomers being the most promising structures. Furthermore, the proposed mode of action was supported by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…2-[ N -(4-methoxybenzyl)aminomethyl]-4-phenyl-1-azabicyclo[2.2.1]heptane 7 was chosen on the basis of its similarity to the side chain present in quinine 1 and based on our in-house knowledge pertaining to the synthesis of this class of compounds. A series of 1-azabicyclo[2.2.1]heptanes had previously been synthesized in our group and evaluated for in vitro antiplasmodium activity [ 32 ]. Based on in silico docking studies of the most active compound, the moderate antiplasmodium activity observed was hypothesized to (partially) be attributed to inhibition of plasmepsin II, an enzyme essential for hemoglobin digestion in the parasite [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2-[ N -(4-methoxybenzyl)aminomethyl]-4-phenyl-1-azabicyclo[2.2.1]heptane 7 was chosen on the basis of its similarity to the side chain present in quinine 1 and based on our in-house knowledge pertaining to the synthesis of this class of compounds. A series of 1-azabicyclo[2.2.1]heptanes had previously been synthesized in our group and evaluated for in vitro antiplasmodium activity [ 32 ]. Based on in silico docking studies of the most active compound, the moderate antiplasmodium activity observed was hypothesized to (partially) be attributed to inhibition of plasmepsin II, an enzyme essential for hemoglobin digestion in the parasite [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…A series of 1-azabicyclo[2.2.1]heptanes had previously been synthesized in our group and evaluated for in vitro antiplasmodium activity [ 32 ]. Based on in silico docking studies of the most active compound, the moderate antiplasmodium activity observed was hypothesized to (partially) be attributed to inhibition of plasmepsin II, an enzyme essential for hemoglobin digestion in the parasite [ 32 ]. Therefore, it seemed reasonable to explore whether or not the observed moderate antiplasmodium activity could contribute to a potential dual mode of action in our target analogues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…as new azaheterobicyclic scaffolds which displayed strong binding interaction with Plm II in in-silico studies(73). Structure based virtual screening led to discovery of a novel non-peptide Plm II inhibitor (compound 69,Figure 24) with moderate potency (IC 50 =4.6 µM)(74).…”
mentioning
confidence: 99%
“…Quinolines interact and form a non-covalent complex with heme and also inhibit the synthesis of hemozoin. On the other hand, quinuclidine(1-azabicyclo [2.2.2]octane), synthesized by Loffler and Stieze in 1909, is a structural component of some biomolecules, including quinine 10,11 . Although development of a new drug candidate against a specific disease is a difficult task, with the help of informatics-driven chemistry, it is now fairly easy.…”
mentioning
confidence: 99%